2021
DOI: 10.1002/jbm.a.37336
|View full text |Cite
|
Sign up to set email alerts
|

3D bioprinting of photo‐crosslinkable silk methacrylate (SilMA)‐polyethylene glycol diacrylate (PEGDA) bioink for cartilage tissue engineering

Abstract: Articular cartilage damage poses huge burden on healthcare sector globally due to its extremely weak inherent regenerative ability. Three-dimensional (3D) bioprinting for development of cartilage mimic constructs using composite bioinks serves as an emerging perspective. However, difficulty in development of suitable bioink and chemical crosslinking associated inherent toxicity hamper widespread adoption of this technique. To circumvent this, a photo-polymerizable hydrogel-based bioink

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 63 publications
(153 reference statements)
0
24
0
Order By: Relevance
“…PEGDA and PEGMA have been mixed with other polymers, such as alginate, to increase viscosity. In particular, PEGDA is a promising biomaterial for CTE since it can be injectable less invasively and can differentiate the MSCs into chondrocyte-like cells in in vitro conditions . Skaalure et al developed a new biodegradable cartilage-specific PEG-based hydrogel and encapsulated bovine chondrocytes for cartilage tissue engineering .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEGDA and PEGMA have been mixed with other polymers, such as alginate, to increase viscosity. In particular, PEGDA is a promising biomaterial for CTE since it can be injectable less invasively and can differentiate the MSCs into chondrocyte-like cells in in vitro conditions . Skaalure et al developed a new biodegradable cartilage-specific PEG-based hydrogel and encapsulated bovine chondrocytes for cartilage tissue engineering .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, PEGDA is a promising biomaterial for CTE since it can be injectable less invasively and can differentiate the MSCs into chondrocytelike cells in in vitro conditions. 58 Skaalure et al developed a new biodegradable cartilage-specific PEG-based hydrogel and encapsulated bovine chondrocytes for cartilage tissue engineering. 59 De France et al have designed an in situ gelling nanocomposite hydrogel based on PEGMA and rigid rodlike cellulose nanocrystals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to printing technologies, the formulation of bio-inks, usually in the combination of supportive biomaterials and specific cell types, is critical for the success of bioprinting. The biomaterials used in bioprinting can be roughly divided into two subtypes: (1) natural biomaterials, such as alginate [ 14 , 35 , 36 , 37 ], agarose [ 35 , 38 ], collagen [ 39 , 40 ], and nanocellulose [ 41 ]; and (2) synthetic biomaterials, such as polyethylene glycol diacrylate (PEDGA) [ 42 ], and Pluoronic ® [ 43 , 44 ]. Each material has unique mechanical (e.g., printability) and biological properties (e.g., the ability to support long-term cell adhesion and growth).…”
Section: Bioprinting: Methods and Materialsmentioning
confidence: 99%
“…In recent years various types of hydrogels based on natural and synthetic polymers were employing multiple different cross-linking mechanisms. It has been shown that the appropriate choice of chemical cross-linking approach leads to the generation of hydrogel networks with properties tailored to the desired clinical or tissue engineering application. Among all types of hydrogels, peptide- and protein-based hydrogels have been widely studied as biocompatible matrices for numerous biomedical applications. , These molecules typically form safe and effective biomaterials due to their ability to form stable networks under mild conditions, their excellent intrinsic biocompatibility, as well as tunable biochemical and biophysical properties. ,,, Their physical and biochemical properties depend on the composition, the polymerization method, and the type and degree of cross-linking . The utilization of cross-linking approaches has led to the development of many applications for these hydrogels in biomedical science, especially in designing injectable cell and drug cargo vehicles. ,, Moreover, they have become an integral part of 3D culture research to investigate the cellular proliferation and migration as well as interactions between encapsulated cells (cell–cell) and cells with the matrix (cell–material). , Since they mimic the structure and characteristics of extracellular matrix (ECM), they appear as ideal mimicking biomaterials for many biomedical applications. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…This component is widely utilized in the preparation of photo-cross-linkable hydrogels that are cured using light. In addition, PEGDA hydrogels are bioinert, nontoxic, nonimmunogenic, possess tunable physical and chemical properties, and have been shown to be injectable. , Bandyopadhyay et al have developed a bioink made of composite bioink in order to promote cartilage regeneration (Figure B) . SFMA, PEGDA, and gelatin have been used as the main components of their bioink.…”
Section: Chemical Modification Of the Sf For Introducing The Methacry...mentioning
confidence: 99%